(untitled) (Historia, 2021)
A number of scholars have explored the development of the Livingstone Museum and the role it played in colonial and post-colonial Zambia. Those who did so during the colonial period include Brelsford, Clark, Gluckman, Jones, Humphrey and Clay.They discussed the evolution of museums in general, noting that firstly, their purpose was to acquire, select and preserve material culture; secondly, to add knowledge; and thirdly to diffuse that knowledge to the general public. They also highlighted the origins of Livingstone Museum, the reasons for its establishment and the policy governing it during its formative years. According to Clark, the museum’s policy was to interpret and show the history, development and status of the people resident in the country and to offer that knowledge to the public. He saw the role of the museum as a “liaison institution between the European settlers and African ethnic groups, bringing to both, closer understanding of each other, their modes of life, manufacturing, social and economic history and development”. On the other hand, W.V. Brelsford, an administrative officer in the colonial government of Northern Rhodesia, discussed the role of museums from the administrative point of view. According to him, “many of the exhibits in the museum’s care ought to inform the administrator of the traditions and beliefs that may long continue to assert their influence over the lives of his people”. He believed that through a detailed study of exhibits, intimate knowledge could be acquired on the ethnic groups. On the other hand, M.C. Humphrey, a European settler, discussed European settlers’ expectations from museums during the colonial period. He wanted to “learn something of man (sic) [people] in Northern Rhodesia in an easy and interesting way”. He also called for the creation of small sections in the museum whereAfricans could learn about the “white man’s progress”, and felt that a section showing “the effect of European influence upon African culture in series according to the varying degrees of impurity”, was desirable.